Inorganic-Organic Nanocomposite Assembly Using Collagen as a Template and Sodium Tripolyphosphate as a Biomimetic Analog of Matrix Phosphoprotein - Dai, Lin; Qi, Yi-Pin; Niu, Li-Na; Liu, Yan; Pucci, Cesar R. [UNESP]; Looney, Stephen W.; Ling, Jun-Qi; Pashley, David H.; Tay, Franklin R. (Amer Chemical Soc, 2011)
Nanocomposites created with polycarboxylic acid alone as a stabilization agent for prenucleation clusters-derived amorphous calcium phosphate exhibit nonperiodic apatite deposition. In the present study, we report the use of inorganic polyphosphate as a biomimetic analog of matrix phosphoprotein for directing poly(acrylic acid)-stabilized amorphous nano-precursor phases to assemble into periodic apatite-collagen nanocomposites. The sorption and desorption characteristics of sodium tripolyphosphate to type I collagen were examined. Periodic nanocomposite assembly with collagen as a template was demonstrated with TEM and SEM using a Portland cement-based resin composite and a phosphate-containing simulated body fluid. Apatite was detected within the collagen at 24 h and became more distinct at 48 h, with prenucleation clusters attaching to the collagen fibril surface during the initial infiltration stage. Apatite-collagen nanocomposites at 72 h were heavily mineralized with periodically arranged intrafibrillar apatite platelets. Defect-containing nanocomposites caused by desorption of TPP from collagen fibrils were observed in regions lacking the inorganic phase.